Opsonophagocytic activity following a reduced dose 7-valent pneumococcal conjugate vaccine infant primary series and 23-valent pneumococcal polysaccharide vaccine at 12 months of age - Russell, F.M. (2014)
10.1016/j.vaccine.2010.10.046